Frontier technologies: A window of opportunity for leapfrogging! - Liu Zhenmin (UN Chronicle, 2019)
Imagine a world with no hunger, where every child attends school and no one dies from a communicable disease. This is not a utopian dream, but rather our collective vision for a society where no one is left behind. It serves as our guiding spirit—our raison d’être—as we work together towards the implementation of the 2030 Agenda for Sustainable Development. Frontier technologies offer us considerable hope for a sustainable future.